Synthesis and characterization of boiled linseed oil integrated with and without reduced graphene oxide nanosheets blended microcapsules - P John Prathap Singh; A Vasanthanathan (Materials Research Express)
The synthesis and characterization of reduced graphene oxide, boiled linseed oil(BLO), and reduced graphene oxide(rGO)—boiled linseed oil microcapsules (BLO-rGO MCs) are effectuated. The synthesis of reduced graphene oxide involved the reduction of graphene oxide using a reducing agent, resulting in the formation of reduced graphene oxide sheets with a high degree of reduction. Characterization techniques such as XRD and FTIR confirmed the successful reduction of graphene oxide to reduced graphene oxide. Boiled linseed oil was characterized using FTIR and SEM techniques, which revealed the molecular structure and surface morphology of the BLO. These microcapsules were synthesized using a simple and scalable method that involves the encapsulation of reduced graphene oxide and boiled linseed oil within a protective shell. The microcapsules were characterized using various techniques such as SEM, FTIR, and XRD, which evidently demonstrated the successful encapsulation of reduced graphene oxide and boiled linseed oil as microcapsules. The combination of reduced graphene oxide and boiled linseed oil as microcapsules offers unique properties such as improved stability, controlled release, as well as increased functionality. These microcapsules have potential applications in numerous fields such as coatings, composites, and drug delivery. The overall output of this study demonstrates the high possibility for the development of novel materials with unique properties and potential applications in numerous fields via the synthesis and characterization of reduced graphene oxide, boiled linseed oil, and reduced graphene oxide-boiled linseed oil microcapsules.